Environmental fluctuation: player awareness and adaptability in platform adventure game - Leong, Xue Qian (2024)

(untitled)
Like Little Nightmares, Chroma Journey is a 2.5D platform adventure game. As the four Auspicious Beasts created Chroma, the player will take control of this guardian, who must reveal the evil existence of the Four Fiends to bring peace back to the planet. The game's goal is to have the player explore intriguing landscapes, solve puzzles, and navigate shadowy areas to reclaim the power of The Four Auspicious Beasts and reseal The Four Fiends.